Anti-biofilm and anti-virulence effects of zerumbone against Acinetobacter baumannii. Issue 8 (28th August 2020) - Kim, Hye-Rim; Shin, Da-Seul; Jang, Hye-In; Eom, Yong-Bin
Abstract : Acinetobacter baumannii is a multidrug-resistant opportunistic pathogen that affects patients with a compromised immune system and is becoming increasingly important as a hospital-derived infection. This pathogen is difficult to treat owing to its intrinsic multidrug resistance and ability to form antimicrobial-tolerant biofilms. In the present study, we aimed to assess the potential use of zerumbone as a novel anti-biofilm and/or anti-virulence agent against A. baumannii . The results showed that zerumbone at sub-inhibitory doses decreased biofilm formation and disrupted established A. baumannii biofilms. The zerumbone-induced decrease in biofilm formation was dose-dependent based on the results of microtitre plate biofilm assays and confocal laser scanning microscopy. In addition, our data validated the anti-virulence efficacy of zerumbone, wherein it significantly interfered with the motility of A. baumannii . To support these phenotypic results, transcriptional analysis revealed that zerumbone downregulated the expression of biofilm- and virulence-associated genes ( adeA, adeB, adeC and bap ) in A. baumannii . Overall, our findings suggested that zerumbone might be a promising bioactive agent for the treatment of biofilm- and virulence-related infections caused by multidrug-resistant A. baumannii .